Efficiency evaluation of different TiO 2 coatings on the photocatalytic inactivation of airborne bacterial spores - Zacarias, Silvia Mercedes (2012)
The performance of different TiO 2 coatings is compared for the photocatalytic inactivation of dry Bacillus subtilis spores dispersed on TiO 2 films under UV-A radiation. Three different TiO 2 coatings were assayed: Degussa P-25, sol-gel, and composite sol-gel/Degussa P-25. The influence of the increase in the number of TiO 2 layers was also studied. Furthermore, the amount of TiO 2 deposited on the borosilicate glass plates and the fraction of energy effectively absorbed by the catalytic films were determined. Spectral diffuse transmittance and reflectance measurements were performed using a spectroradiometer with an integrating-sphere attachment. The net-radiation method was then applied to evaluate the fraction of energy absorbed by the coatings. To objectively compare the performance of the catalytic films, two types of efficiencies were calculated: the photonic efficiency and the quantum efficiency of inactivation. The highest quantum efficiency was obtained with the TiO 2 Degussa P-25 coating with two layers. © 2012 American Chemical Society.